Transient cross flow and heat transfer over a rotationally oscillating cylinder subjected to gust impulse. (July 2019) - Yawar, Arsalan; Ebrahem, M.; Manzoor, S.; Sheikh, N.A.; Ali, Muzaffar
Highlights: Effect of gust is numerically studied on rotationally-oscillating cylinder in lock-on. Secondary frequencies and transient amplification of lift are induced due to gust. Transient amplification of lift may lead system out of lock-on temporarily. Gust introduces phase shift between angular velocity and lift. Phase shift causes early vortex detachment and shear layer stretching. Overall convective heat transfer physics is affected by gust. Abstract: Numerical analysis is carried out to investigate the effect of an upstream gust-impulse on the transient fluid flow and associated convective heat transfer from a two dimensional rotationally oscillating circular cylinder. Three distinct oscillation scenarios based on the oscillation amplitude are investigated. Forcing frequency for each rotational amplitude is varied such that the system remains within the lock-on state. Further, three different gust scenarios are chosen by relating the gust frequency, StG, to the natural vortex shedding frequency in the streamlined flow for a fixed Reynolds number of 110 at Prandtl number of 7. Balances for mass, momentum, and energy are solved by considering incompressible, viscous fluid subjected to no-slip CWT boundary at the cylinder wall. Phase diagrams, the spatiotemporal mean of the pressure coefficient and Nusselt number i.e. C P ‾ ‾ and Nu ‾ ‾, and vorticity and temperature contours are presented and discussed in detail. Temporal evolution of lift coefficient ( CL ) and Lissajous curves of lift coefficient against drag coefficient depict the perturbing effect of the gust-impulse. Time averaged drag coefficient ( C D ‾ ) and RMS values of lift coefficient ( CL -RMS ) show contrasting shifts in their peak values as the rotational-oscillation amplitude is increased. In addition to causing a transient phase difference between the cylinder angular velocity and the lift coefficient, introduction of the gust-impulse in the flow domain induces secondary frequencies causing transient amplification of the lift force which tends to make the system temporarily unstable by shifting it out of the lock-on state. The induced phase difference causes short term shear layer stretching and early vortex detachment around the cylinder surface thereby affecting the overall flow and the resultant convective heat transfer physics in the system. Moreover, a regression correlation is presented relating the oscillation amplitude, oscillation forcing Strouhal frequency and gust Strouhal frequency to the spatiotemporal averaged Nusselt number.